Mathematical Statistics / Fifth Edition - Freund John E (Prentice Hall International, 1992)
Preface, Introduction, Probability, Estimation: Theory, Estimation: Applications, Hypothesis Testing: Theory, Hypothesis Testing: Applications, Regression and Correlation, Analysis of Variance, Nonparametric Tests, Appendix: Sums and Products, Statistical Tables, Answers to Odd-Numbered Exercises, Index.